Optimization of Copper Dissolution from Electronic Waste Printed Circuit Board Using Leaching Method - Faradisa Athalla; Erni Sulistiawati; Iwan Setiawan (JURNAL SAINS NATURAL, 2022)
Electronic waste contains hazardous materials which have an adverse impact on the environment. Therefore, a solution is needed to recycle electronic waste. One solution is recovering copper metal from the Printed Circuit Board (PCB) in electronic waste. The dissolution of copper is carried out by the leaching method, which means dissolving copper using a selective solvent. Analysis of copper was performed using Inductively Coupled Plasma-Optical Emission Spectroscopy (ICP-OES). This experiment aims to determine the factors that influence the optimization of copper dissolution from PCB electronic waste by leaching method and analysis the copper content using ICP-OES. The primary data obtained is the per cent recovery of each factor that affects copper dissolution, which is the concentration of sulfuric acid as a solvent, the percentage of solid / liquid, the speed of stirring, the temperature, and the length of stirring. The optimum conditions were achieved in the form of the highest recovery in each variation, which is 9.8% sulfuric acid, 5% solid/liquid percentage, 200 rpm stirring speed, and at temperature 60 °C with a stirring time of 120 minutes, the per cent recovery was obtained respectively 79.83%; 74.86%; 76.52%; and 54.84%.Keywords: electronic, waste,  PCB, dissolution, copper Optimalisasi Pelarutan Tembaga dari Limbah Elektronik Printed Circuit Board dengan Metode LeachingABSTRAKLimbah elektronik mengandung bahan-bahan berbahaya yang berdampak buruk bagi lingkungan. Oleh sebab itu, diperlukan solusi untuk mendaur ulang limbah elektronik salah satunya adalah pengambilan kembali atau recovery logam tembaga dari Printed Circuit Board (PCB) pada limbah elektronik. Pelarutan tembaga dilakukan dengan metode leaching, yaitu dengan melarutkan tembaga menggunakan pelarut yang selektif. Analisis terhadap kadar tembaga dilakukan menggunakan Inductively Coupled Plasma-Optical Emission Spectroscopy (ICP-OES). Percobaan ini bertujuan untuk mendapatkan faktor-faktor yang berpengaruh pada optimalisasi pelarutan tembaga dari limbah elektronik PCB dengan metode leaching dengan analisis terhadap kadar tembaga menggunakan ICP-OES. Data primer yang diperoleh adalah persen recovery dari setiap faktor-faktor yang memengaruhi pelarutan tembaga, yaitu konsentrasi asam sulfat sebagai pelarut, persentase solid/liquid, kecepatan pengadukan, suhu, dan lama pengadukan. Kondisi optimum yang dicapai berupa recovery tertinggi pada setiap variasi, yaitu pada 9,8% asam sulfat, persentase 5% solid/liquid, kecepatan pengadukan 200 rpm, dan suhu pada 60 °C dengan lama pengadukan 120 menit diperoleh persen recovery secara berturut-turut 79,83%; 74,86%; 76,52%; dan 54,84%.Kata kunci : elektronik, limbah,  PCB, pelarut, tembaga